Disparate thermostability profiles and HN gene domains of field isolates of Newcastle disease virus from live bird markets and waterfowl in Uganda - Omony, John B.; Wanyana, Agnes; Mugimba, Kizito K.; Kirunda, Halid; Nakavuma, Jessica L.; Otim-Onapa, Maxwell; Byarugaba, Denis K. (Virology Journal, 2016)
Uganda poultry production is still faced with frequent outbreaks of Newcastle disease (ND) in the backyard free-range systems despite the accessibility of cross protective vaccines. Live bird markets and waterfowl has long been reported as a major source of disease spread as well as potential sources of avirulent strains that may mutate to virulent strains. ND-virus has been reported enzootic in Ugandan poultry but limited studies have been conducted to ascertain thermostability phenotypes of the Ugandan ND-virus strains and to understand how these relate to vaccine strains. Methods: This study evaluated thermostability of 168 ND-virus field isolates recovered from live bird markets and waterfowls in Uganda compared to two live commercial vaccine strains (I2 and LaSota) by standard thermostability procedures and Hemagglutinin-Neuraminidase (HN) gene domains. The known pathotypes with thermostability profiles were compared at HN amino acid sequences. Results: Field isolates displayed disparate heat stability and HN gene domains. Thermolabile isolates were inactivated within 15 min, while the most thermostable isolates were inactivated in 120 min. Four thermostable isolates had more than 2 log2 heamaglutinin (HA) titers during heat treatment and the infectivity of 9.8 geometric mean of log10 EID50 % in embryonated eggs. One isolate from this study exhibited a comparable thermostability and stable infectivity titers after serial passages, to that of reference commercial vaccine was recommended for immunogenicity and protection studies. Conclusion: The occurrence of ND-virus strains in waterfowl and live bird markets with disparate thermostability and varying HN gene domains indicate circulation of different thermostable and thermolabile ND-virus pathotypes in the country.
Keywords: Thermostability; Infectivity; Thermostable isolate; Hemagglutionation assay